Effect of constitutive inactivation of the myostatin gene on the gain in muscle strength during postnatal growth in two murine models. Issue 2 (12th November 2016) - Stantzou, Amalia; Ueberschlag‐Pitiot, Vanessa; Thomasson, Remi; Furling, Denis; Bonnieu, Anne; Amthor, Helge; Ferry, Arnaud
ABSTRACT: Introduction : The effect of constitutive inactivation of the gene encoding myostatin on the gain in muscle performance during postnatal growth has not been well characterized. Methods : We analyzed 2 murine myostatin knockout (KO) models, (i) the Lee model (KO Lee ) and (ii) the Grobet model (KO Grobet ), and measured the contraction of tibialis anterior muscle in situ . Results : Absolute maximal isometric force was increased in 6‐month‐old KO Lee and KO Grobet mice, as compared to wild‐type mice. Similarly, absolute maximal power was increased in 6‐month‐old KO Lee mice. In contrast, specific maximal force (relative maximal force per unit of muscle mass was decreased in all 6‐month‐old male and female KO mice, except in 6‐month‐old female KO Grobet mice, whereas specific maximal power was reduced only in male KO Lee mice. Conclusions : Genetic inactivation of myostatin increases maximal force and power, but in return it reduces muscle quality, particularly in male mice. Muscle Nerve 55 : 254–261, 2017